The synergistic effect of TiO2 nanoporous modification and platelet-rich plasma treatment on titanium-implant stability in ovariectomized rats - Jiang N (Dove Medical Press, 2016)
Nan Jiang,1,2 Pinggong Du,2 Weidong Qu,2 Lin Li,2 Zhonghao Liu,2 Songsong Zhu1 1State Key Laboratory of Oral Diseases and Department of Oral and Maxillofacial Surgery, West China Hospital of Stomatology, Sichuan University, Chengdu, 2Yantai City Stomatological Hospital, Yantai, People’s Republic of China Abstract: For several decades, titanium and its alloys have been commonly utilized for endosseous implantable materials, because of their good mechanical properties, chemical resistance, and biocompatibility. But associated low bone mass, wear and loss characteristics, and high coefficients of friction have limited their long-term stable performance, especially in certain abnormal bone-metabolism conditions, such as postmenopausal osteoporosis. In this study, we investigated the effects of platelet-rich plasma (PRP) treatment and TiO2 nanoporous modification on the stability of titanium implants in osteoporotic bone. After surface morphology, topographical structure, and chemical changes of implant surface had been detected by scanning electron microscopy (SEM), atomic force microscopy, contact-angle measurement, and X-ray diffraction, we firstly assessed in vivo the effect of PRP treatment on osseointegration of TiO2-modified implants in ovariectomized rats by microcomputed tomography examinations, histology, biomechanical testing, and SEM observation. Meanwhile, the potential molecular mechanism involved in peri-implant osseous enhancement was also determined by quantitative real-time polymerase chain reaction. The results showed that this TiO2-modified surface was able to lead to improve bone implant contact, while PRP treatment was able to increase the implant surrounding bone mass. The synergistic effect of both was able to enhance the terminal force of implants drastically in biomechanical testing. Compared with surface modification, PRP treatment promoted earlier osteogenesis with increased expression of the RUNX2 and COL1 genes and suppressed osteoclastogenesis with increased expression of OPG and decreased levels of RANKL. These promising results show that PRP treatment combined with a TiO2-nanomodified surface can improve titanium-implant biomechanical stability in ovariectomized rats, suggesting a beneficial effect to support the success of implants in osteoporotic bone. Keywords: TiO2 nanotubes, PRP, titanium implants, ovariectomized rats